Biosorption of lead from simulated industrial wastewaters by aquatic bryophytes - Martins, Ramiro (2007)
Aquatic bryophytes are frequently used as biomonitors for trace metals in aquatic ecosystems. Nevertheless, their special characteristics also allow using them as biosorbents to clean industrial wastewaters. As biosorption is a low cost and effective method for treating metal-bearing wastewaters, understanding the kinetics process is relevant for design purposes. In this study, the performance of the aquatic bryophyte Fontinalis antipyretica for removing lead from simulated wastewaters has been evaluated. Three kinetic models (pseudo-first order, pseudo-second order and Elovich) were fitted to the experimental data and compared using a Test-F. Previously, the effect of parameters such as the initial solution pH, contact time and initial metal ion concentration, on biosorption was investigated. The initial pH of the solution was found to have an optimum value is in the range 4.0-6.0. The equilibrium sorption capacity of lead by Fontinalis antipyretica increased with the initial metal concentration. For an initial metal concentration of 10 mg L-1, the uptake capacity of the moss, at equilibrium, is 4.8 mg g-1. Nevertheless, when the initial concentration increases up to 100 mg L-1, the uptake of lead is 10 times higher. The pseudo-second order biosorption kinetics provided the better correlation with the experimental data . The applicability of the Langmuir and Freundlich adsorption isotherms for the present system was tested. The maximum sorption capacity of mosses was 68 mg g-1.